DEVELOPMENT MODULE BASED ON REALISTIC MATHEMATICS EDUCATION ON STUDENT'S MATHEMATIC CONNECTION SKILLS - Gunawan Gunawan; Ratna Fitrianingsih; Lukmanul Akhsani; Eka Setyaningsih; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2022)
This study aims to produce a mathematics learning module based on Realistic Mathematical Education (RME) that meets the aspects of validity and practicality and effectively improves students' mathematical connection skills. This study uses a 4D development model that has been modified into three stages; define, design, and develop. The trial was conducted at SMP Negeri 1 Cilongok with 11 students in class VIII E. The results showed that the developed mathematics learning module was valid by obtaining an average score of 4.3. The teacher's response showed an average score of 4.2 and 3,9 which means that the practical mathematics module is used in the teaching and learning process. The results of the effectiveness are carried out through the results of the pretest and posttest. The test was carried out through the N-Gain trial and obtained an average score of 0.5731, which was interpreted as average